Rozwój nauki i kultu «Matki Bożej Opatrzności» - Adam Wojtczak (Wrocławski Przegląd Teologiczny)
The above title was not directly derived from the Holy Scripture. It is difficult to determine who first used it or which prevailed in the history of the Church: teaching about the Mother of Divine Providence or Her cult. These two realities have interwoven over the centuries to such a degree that theological reflection deepens the service of Mary, which in turn inspires theologians to reflect on Mary. The Fathers of the Church long ago pointed at Mary’s participation in the plans of Divine Providence. They perceived Her as the Mother of Christ who completed the work of redemption. The Middle Ages emphasized Her providential participation in the Mystery of Christ’s cross. The Barnabites contributed a great deal to the development of the cult of the Mother of Divine Providence. They have been spreading the cult, wherever they serve, since the 17th century under the influence of Mary’s interventions in their lives and pastoral ministry. Since the turn of the 19th and 20th centuries the Magisterium of the Church has frequently referred to Mary. Although rarely making use of the title, post-counciliar popes explain its theological significance. John Paul II emphasized the judgments of the Divine Providence concerning Mary. Benedict XVI focuses on Mary’s acceptance of those judgments and on the resulting salvific fruits for us. The symptoms of the teaching and cult of the Mother of Divine Providence are also evident in the Polish Church. Since the Middle Ages – within the universal Church alike – the references of Mary to the Divine Providence have been more often seen in sermons, songs and catecheses than in the use of the title itself. Over the last years, especially due to the introduction of the Mass formulary of the Mother of Divine Providence, Her cult has been steadily developing along with the intensifying theological reflection on the title.